2021
DOI: 10.1093/cercor/bhab376
|View full text |Cite
|
Sign up to set email alerts
|

PET Metabolic Imaging of Time-Dependent Reorganization of Olfactory Cued Fear Memory Networks in Rats

Abstract: Memory consolidation involves reorganization at both the synaptic and system levels.The latter involves gradual reorganization of the brain regions that support memory and has been mostly highlighted using hippocampal-dependent tasks. The standard memory consolidation model posits that the hippocampus becomes gradually less important over time in favor of neocortical regions. By contrast, this reorganization of circuits in amygdala-dependent tasks has been less investigated. Moreover, this question has been ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 119 publications
(108 reference statements)
0
13
0
Order By: Relevance
“…Moreover, this plasticity also exhibits time-dependent properties, more prominent in long-term threat memory (Hegoburu and others 2014; Mouly and others 2022; You and others 2022) (Fig. 1B).…”
Section: Olfactory Cortex—a Model System For Study Of the Sensory Thr...mentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, this plasticity also exhibits time-dependent properties, more prominent in long-term threat memory (Hegoburu and others 2014; Mouly and others 2022; You and others 2022) (Fig. 1B).…”
Section: Olfactory Cortex—a Model System For Study Of the Sensory Thr...mentioning
confidence: 95%
“…1B). Notably, applying neuroimaging methods (fMRI and PET) for large-scale, whole-brain analysis combined with temporal profiling of associative plasticity over a long delay, two new studies (in rodents and humans) demonstrated that the piriform cortex exhibits associative plasticity both soon and long after threat conditioning, in contrast to transitory (or no) plasticity in the amygdala and frontal cortices (Mouly and others 2022; You and others 2022). These effects are consistent with findings from human fMRI and electrophysiologic studies in the visual and auditory cortices, which indicated lasting associative plasticity in the sensory cortex in contrast to transitory plasticity in the amygdala and inferotemporal and orbitofrontal cortices (Apergis-Schoute and others 2014; You and others 2021).…”
Section: Olfactory Cortex—a Model System For Study Of the Sensory Thr...mentioning
confidence: 99%
“…The brain networks recruited in Where rats, that show an incomplete memory, are more restricted and less efficient in terms of functional connectivity and specific to networks of memories with contextual and spatial information (dorsal hippocampus, retrosplenial cortex, and habenula) 46–50 . In contrast, WWW rats that remember all episodic information recruit larger brain networks, including the same spatial network and brain regions that are functionally connected and implicated in olfactory memory (piriform, lateral entorhinal, orbitofrontal, prelimbic and infralimbic cortices) 5156 . A comparison of the Where and WWW profiles reveals that complete recollection of remote episodic memory recruits a core network of interconnected brain regions (medio-lateral orbitofrontal, ventral CA1 and basolateral amygdala) 57–62 that are implicated in the valence and emotional processing of information and directly correlated with memory accuracy during recall.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, we concluded that aged CA1 neurons are more plastic compared to aged PC neurons. As sensory cortices are the more permanent repertoire of long‐term memory, [ 37–39 ] our results may suggest that conversion of short‐term memory (initially encoded in the hippocampus) to long‐term memory storage becomes more challenging in aged animals.…”
Section: Discussionmentioning
confidence: 99%